Mixed-mode Zentangle and Pastel Nagomi artwork for improving mental well-being in university students during COVID-19 pandemic – a randomized controlled feasibility trial - Cheung, Kin; Ma, Ka Yan; Tsang, Hilda; Leung, Nok Hang; Lui, Ka Yee; Ho, Sze Wing (Frontiers in Psychology, 2023)
Background University students are identified as a high-risk group for mental health problems. Artworks have been found effective in enhancing individuals’ mental well-being in different populations, but none have been conducted on university students. This study was to address this research gap to determine the feasibility and estimate the preliminary effects of Zentangle and Pastel Nagomi on the mental well-being of undergraduate students during the COVID-19 pandemic. Method This was a 3-arm randomized controlled trial, with 33 undergraduates allocated to two 8-week artworks (Zentangle or Pastel Nagomi Art group) and a control group. Data were collected at baseline, and weeks 4, 6, 8, and 12. Focus group interviews were conducted at the 12-week follow-up. Results The consent and attrition rates were 80.5 and 6.06%, respectively. The attendance rate ranged from 83.3 to 100%. Compared with the control group, the Pastel Nagomi art group had a significant improvement in retaining positive affect at week 6. This retention could be further observed at week 12. Moreover, the Zentangle group had a significant increase in positive affect at week 4, with better retention at week 12. In addition, the within-group analyses showed that the Pastel Nagomi art group had significantly decreased negative affect at weeks 6 and week 12; and the Zentangle group had significantly decreased depression at week 8. The qualitative findings suggested that the intervention resulted in the participants enjoying the artwork process, and being proud of their artwork and personal growth. Limitation The study included an imbalance number of online vs. face-to-face sessions, and repeated measures may have affected the results. Conclusion The study suggests that both artworks are effective in improving undergraduates’ mental well-being and that it is feasible to conduct future large-scale studies (263 words).